RELEVANSI MODUL AJAR BERBASIS KONTEKS LOKAL PADA PEMBELAJARAN IPAS DI SDN BOGEM 1 - Wulanda Febiani; Cristian yudha Asmara; Khoirina Bilkisti; Muhammad Imaduddin; Arif Mahya Fanny (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was triggered by the need to implement learning modules that focus on local contexts in IPAS in the Independent Curriculum so that the learning process becomes more relevant, valuable and connected to students' daily lives. However, there are several challenges in its implementation, such as less than optimal development of teaching materials, limitations in learning resources, and assessments that tend to focus on cognitive aspects. This research aims to explore how to implement local context-based teaching modules at SDN Bogem 1 and to evaluate their relationship with students' daily life and culture. Qualitative methods with a descriptive approach were used in this research, focusing on class III teachers, school principals, and students at SDN Bogem 1 as research subjects. Data was collected through observation, interviews and documentation. Data analysis was carried out using the Miles and Huberman analysis model, which includes data reduction, data presentation and conclusion drawing, while checking the validity of the data was carried out through triangulation. The findings from this research indicate that the implementation of local context-based teaching modules at SDN Bogem 1 has been implemented well. The teachers have utilized teaching modules in line with the Independent Curriculum, connecting lesson material with the surrounding environment, incorporating elements of local wisdom, and implementing different learning approaches. However, there is still a need to increase the variety of learning resources, learning media, in-depth integration of local culture, as well as assessments that cover cognitive, affective and psychomotor aspects in a balanced way. Therefore, learning based on local contexts is considered to be able to contribute to creating more relevant and meaningful learning experiences for students.